Placing the Dead in the Postmemory of the Cheju Massacre in Korea - Kim, Seong Nae (The journal of religion, 2019)
The article offers information on the workshop "Bordering Religions in (Post-) Cold War Worlds" that was held at the Higher School of Economics in St. Petersburg in June 2016. It focuses on the domestic and international influences on Cheju Island. It focuses on the Asia-Pacific, a geographic zone that experienced decolonization involving vicious civil wars and political violence.